KABUKI SYNDROME - Doina Maria Ioan; Andrei Zamfirescu (Amaltea Medical Publishing House, 2008)
Kabuki (Niikawa-Kuroki) syndrome (KS) is a condition of unknown etiology, characterized by a pentad of cardinal signs and symptoms: mental retardation, peculiar facies oriental-like, dermatoglyphic abnormalities including persistent finger and toe pads, skeletal anomalies and postnatal growth retardation. Associated anomalies could be present: cleft lip/palate, visceral, ocular etc. Since the first description of KS in 1981 by Niikawa et al and Kuroki et al, more than 350 cases have been reported. We shortly review the KS emphasizing on the latest Romanian Kabuki patient.